Comparison of the percentage of medical success for Phytovagex vaginal suppository and Metronidazole oral tablet in women with bacterial vaginosis - Farzaneh Jafarnezhad; Mahin Kiyani Mask; Hasan Rakhshandeh; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2017)
Introduction: Bacterial Vaginosis is the most common cause of vaginitis that itself is responsible for 50% of all cases of vaginitis. Metronidazole is considered the first line for treatment, but it is reported that there is carcinogen and resistance to metronidazole. With regard to anti-bacterial effects of medicinal herbs such as Nigella sativa (the trade name of Phytovagex) on microbic organism, this study was done with aim to compare the remedial success percentage of Phytovagex vaginal suppository with Metronidazole oral tablet in women with bacterial vaginosis. Methods: This triple-blind randomized clinical trial was done on 57 women with bacterial vaginosis referred to health centers subclass of health center No 2 in Mashhad at 2015-2016. The research units were randomly divided into intervention and control groups. The intervention group received Phytovagex vaginal suppository 1% once a day and placebo tablet twice a day for seven days, and control group received metronidazole tablet 250 mg twice a day and placebo vaginal suppository once a day for seven days. 7-10 days after treatment, the success percentage of treatment was investigated at each group by clinical standards. Data was analyzed by SPSS software (version 16) and independent t-test, Chi-square, Macnemar and Exact Fisher tests. P< 0.05 was considered significant. Results: The success percentage of treatment of bacterial vaginosis was 74.2% in Phytovagex vaginal suppository group and 69.2% in Metronidazole tablet group that was not statistically significant (P>0.05). Conclusions: Phytovagex vaginal suppository is as effective as Metronidazole tablet in treatment of bacterial vaginosis and can be an appropriate alternative to treat bacterial vaginosis.